Analisis Korelasi antara Efek Proliferasi Limfosit dengan Kandungan Fenolik dan Flavonoid Subfraksi Etil Asetat Myrmecodia tuberosa (Non Jack) Bl. secara In Vitro pada Mencit BALB/C - AKHMAD KHUMAIDI; TRIANA HERTIANI; EDIATI SASMITO (Fakultas Farmasi Universitas Pancasila, 2015)
Ethyl acetate fraction of Myrmecodia tuberosa (non Jack) Bl. expressed potential immunomodulatory effect in preliminary study. This study was aimed to determine the stimulation index of each subfraction towards lymphocyte of BALB/C mice by in vitro technique and to explore the activityof lymphocyte proliferation correlated to total phenolic contents. lymphocyte proliferation assay was performed by MTT. Determination of total flavanoid content was done by a colorimetric method while the total phenolic was tested by the Folin-Ciocalteu method. The result showed stimulation index profile was positively correlated with the total flavanoid content( R2 = 0,606) while weak correlation was observed on the total phenolic content (R2 = 0,167).